2016
DOI: 10.1088/0953-8984/28/35/353002
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy of transition metal dichalcogenides

Abstract: Raman spectroscopy of transition metal dichalcogenides (TMDs) is reviewed based on our recent theoretical and experimental works. First, we discuss the semi-classical and quantum mechanical description for the polarization dependence of Raman spectra of TMDs in which the optical dipole transition matrix elements as a function of laser excitation energy are important for understanding the polarization dependence of the Raman intensity and Raman tensor. Overviewing the symmetry of TMDs, we discuss the dependence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
200
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(217 citation statements)
references
References 94 publications
(185 reference statements)
12
200
1
4
Order By: Relevance
“…Figure a shows the comparison of Raman spectra from triangular and dendritic MoS 2 , MoSe 2 , and MoS 2(1− x ) Se 2 x . TMDs show significant and dominating Raman peaks originating from the in‐plane ( E 2g ) and out‐of‐plane ( A 1g ) vibration modes of chalcogens . It is found that there are no significant changes in peak position and line widths of the Raman modes from dendrite to triangle structures of the same alloy composition.…”
Section: Comparison Of Tafel Slopes Of Triangles and Dendritesmentioning
confidence: 95%
“…Figure a shows the comparison of Raman spectra from triangular and dendritic MoS 2 , MoSe 2 , and MoS 2(1− x ) Se 2 x . TMDs show significant and dominating Raman peaks originating from the in‐plane ( E 2g ) and out‐of‐plane ( A 1g ) vibration modes of chalcogens . It is found that there are no significant changes in peak position and line widths of the Raman modes from dendrite to triangle structures of the same alloy composition.…”
Section: Comparison Of Tafel Slopes Of Triangles and Dendritesmentioning
confidence: 95%
“…Raman spectroscopy has proven to be an important tool in the characterization of low‐dimensional materials and, in particular, in the case of MoS 2 . The first‐order Raman modes of MoS 2 , which involve phonons at the center of the Brillouin zone (BZ), can be used to probe important properties, such as the number of layers, exciton transition energy, stacking effects, interlayer phonons, and defect quantification .…”
Section: Introductionmentioning
confidence: 99%
“…2729 Similarly, the active Raman modes also depend on the crystal symmetry. 26,3741 While the Raman properties of the 2H phase have been extensively studied, 10,42,43 the 1T′ phase has not been fully characterized, and there is significant discrepancy in the literature on the Raman modes assignment as well as the number of modes observed. 13,4450 …”
mentioning
confidence: 99%